Dissolved inorganic antimony, selenium and tin species in water samples from various sampling sites of river vardar in Macedonia and Greece - Serafimovska, Jožica Majda; Arpadjan, Sonja; Stafilov, Trajče; Ilik Popov, Stanko (Society of Chemists and Technologists of Macedonia, 2011)
A highly effective liquid phase semi-microextraction procedure was applied for determination ofultra trace levels of dissolved inorganic species of antimony, tin and selenium in river Vardar (from the 2ndup to 420th km of the river) and its tributaries Crna Reka, Treska, Bregalnica, Pchinja and Lepenec usingelectrothermal atomic absorption spectrometry (ETAAS) for quantification. The concentrations for totaldissolved inorganic antimony were between 6 and 242 ng/l Sb, for Sn(II, IV) – in the range of 2.7–61 ng/lSn and for Se(IV, VI) – in the range of 15–75 ng/l Se. The higher oxidation states of antimony and seleniumwere found as the predominant form in the studied surface waters.